Intimate partner violence as a predictor of marital disruption in rural Rakai, Uganda: a longitudinal study - Wagman, Jennifer A.; Charvat, Blake; Thoma, Marie E.; Ndyanabo, Anthony; Nalugoda, Fred; Ssekasanvu, Joseph; Kigozi, Grace; Serwadda, David; Kagaayi, Joseph; Wawer, Maria J.; Gray, Ronald H. (International journal of public health, 2016)
We assessed the association between intimate partner violence (IPV) and union disruption (divorce or separation) in the rural Ugandan setting of Rakai District. We analyzed longitudinal data collected from April 1999 to June 2006, from 6834 women (15–49 years) living in 50 communities in Rakai. Participants were either married, traditionally married or in a consensual union during one or more surveys and completed at least one follow-up survey. The primary outcome was union disruption through divorce or separation from the primary sexual partner.
Keywords: Intimate partner violence; Union dissolution; Divorce; Global health; Longitudinal analysis; Sub-Saharan Africa